2016
DOI: 10.1167/iovs.16-19325
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Restriction of Neural Activation Using Focused Multipolar Stimulation With a Retinal Prosthesis

Abstract: Citation: Spencer TC, Fallon JB, Thien PC, Shivdasani MN. Spatial restriction of neural activation using focused multipolar stimulation with a retinal prosthesis. Invest Ophthalmol Vis Sci. 2016;57:3181-3191. DOI:10.1167/ iovs.16-19325 PURPOSE. The resolution provided by present state-of-the-art retinal prostheses is severely limiting for recipients, partly due to the broad spread of activation in the retina in response to monopolar (MP) electrical stimulation. Focused multipolar (FMP) stimulation has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 55 publications
(117 reference statements)
6
29
0
Order By: Relevance
“…Multielectrode stimulation has shown promise in improving visual outcomes for retinal implant recipients. Previous studies have shown that simultaneous stimulation with multiple electrodes can increase the number of percepts by activating groups of cells between electrodes 14 and increase resolution by inhibiting current spread 15,16 as compared to singleelectrode stimulation. However, these studies have involved normally sighted animals, limiting the clinical applicability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…Multielectrode stimulation has shown promise in improving visual outcomes for retinal implant recipients. Previous studies have shown that simultaneous stimulation with multiple electrodes can increase the number of percepts by activating groups of cells between electrodes 14 and increase resolution by inhibiting current spread 15,16 as compared to singleelectrode stimulation. However, these studies have involved normally sighted animals, limiting the clinical applicability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, patch recordings in ex vivo retina, Habib et al (2013) showed that a hexapolar configuration limited the spread of retinal activation more than a monopolar configuration, with a pronounced increase in stimulation threshold outside the hex-guard that was not observed at equivalent distances in the monopolar configuration. Similarly, Spencer et al (2016), found that a hexapolar sub-retinal configuration limited the spread of visual cortical activation for near threshold stimulation, when compared to monopolar stimulation. However, Cicione et al (2012) found no significant difference in the spread of cortical activation between these two configurations, at least for stimulation levels approaching saturation.…”
Section: Simultaneous Stimulationmentioning
confidence: 92%
“…This will distort the area of activation toward electrodes sinking the largest fraction of current. To contend with these difficulties a focused multipolar approach ( Figure 8E) has been proposed (Spencer et al, 2016). It overcomes the first limitation by using electrodes across the whole array to distribute the return current from a central stimulating electrode to optimally focus electrical potential.…”
Section: Simultaneous Stimulationmentioning
confidence: 99%
“…Subsequently, Dumm et al evaluated the feasibility of virtual electrodes by current steering in retinal prostheses by varying the ratio of the stimulation current levels between two electrodes and recording the spatial shift of cortical activation patterns evoked by retinal stimulation [118]. Since 2016, this group has utilized the hexagonal configuration for current focusing and steering [119][120][121]. The hexagonal electrode array was supra-choroidally implanted in six normally sighted cats for multipolar stimulation to show not only lowered average voltage levels around the stimulating electrode, but also more focused cortical response patterns than when monopolar stimulation was used [119].…”
Section: Optimization Of Stimulation Patternsmentioning
confidence: 99%
“…Since 2016, this group has utilized the hexagonal configuration for current focusing and steering [119][120][121]. The hexagonal electrode array was supra-choroidally implanted in six normally sighted cats for multipolar stimulation to show not only lowered average voltage levels around the stimulating electrode, but also more focused cortical response patterns than when monopolar stimulation was used [119]. In 2018, the group used the similar electrode array implanted into seven normally sighted cats demonstrating focused stimulation and two-dimensional generation of virtual electrodes using current steering across multiple electrodes [120].…”
Section: Optimization Of Stimulation Patternsmentioning
confidence: 99%